Fonctionnement hydrologique et enjeux de société : exemples de l’aquifère crayeux de l’Ouest du Bassin de Paris - Jean-Paul Dupont (VertigO)
The context of the chalk of the western Paris Basin is chosen here to illustrate the interactions between hydrological processes and human activities. On the plateaus, the input karst is covered by superficial formations more (clay with flints and Quaternary loesses). Runoff produces soil erosion within small watersheds. Runoff and sub-surface flows are swallowed up in sinkholes of the input karst. In this context, sinkholes are the source of the vulnerability of water resources of the chalk aquifer and of geotechnical hazards for human settlements and housing.In valleys, the exploitation of water resources (springs or wells) is affected by the turbid responses to rainfall events. This reflects rapid transports of microbial and chemical contaminants and requires water treatments but also prevention the quality of the water resources. The latter is complex because it must take into account the hydrological environment of numerous sinkholes on plateaus.River flows generally come from the chalk aquifer. In this context, a succession of wet years increases watertable and can generate massive floods (eg, the catastrophic flood of the Somme valley in 1981). The precautionary principle would require removing any human settlements in floodplains. Moreover, the water quality of rivers (eg nitrates) depends on contaminant contents in the unsaturated zone.In conclusion, the chalk karst aquifer of the western Paris Basin is a significant example of the interactions between hydrological processes and human activities : (i) the quality of water resources is conditioned by human activities, and (ii ) land management requires knowledge on hydrological processes and the associated potential risks to property and people.